Green Accounting dan Corporate Social Responsibility (CS): Konsep dan Implementasi dalam Bisnis Berkelanjutan - Bella Sartika; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Green accounting and corporate social responsibility (CSR) are two critical concepts in fostering sustainable business practices. Green accounting emphasizes the inclusion of environmental and social costs in financial reporting, providing companies with a more comprehensive view of their sustainability performance. Meanwhile, CSR involves corporate commitments to societal and environmental welfare, which enhance reputation and stakeholder relations. This article explores the integration of green accounting and CSR, highlighting their benefits, challenges, and implementation strategies. By adopting these approaches, businesses can not only achieve financial growth but also contribute positively to society and the environment.